1996
DOI: 10.1111/j.1540-8191.1996.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Ionized Magnesium Concentrations During Cardiopulmonary Bypass and Their Correlation with Other Circulating Cations

Abstract: Blood iMg depletion occurs frequently in CPB patients. iMg changes are not readily predictable. The association of intraoperative iMg depletion with postsurgical atrial fibrillation--reported to have a hypomagnesemic connection- should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
1
8
0
4
Order By: Relevance
“…
three decades [1][2][3][4][5][6][7][8][9][10][11]. In addition, it is shown that hypomagnesemia following cardiac surgery is associated with an increase in the incidence of dysrhythmia, and Mg administration could contribute to fewer postoperative dysrhythmias [5][6][7] or better myocardial recovery [7].
…”
mentioning
confidence: 98%
“…
three decades [1][2][3][4][5][6][7][8][9][10][11]. In addition, it is shown that hypomagnesemia following cardiac surgery is associated with an increase in the incidence of dysrhythmia, and Mg administration could contribute to fewer postoperative dysrhythmias [5][6][7] or better myocardial recovery [7].
…”
mentioning
confidence: 98%
“…Isto explica, pelo menos em parte, os efeitos benéficos de sua presença no momento da reperfusão, fato que permanecia ainda obscuro quando considerados seus efeitos apenas por ação direta nas musculaturas cardíaca e lisa vascular. Assim, justifica-se sua indicação precoce na vigência do binômio isquemia/reperfusão comum na prática cardiológica moderna incluindo recanalização de artérias após trombólise, angioplastias e particularmente despinçamento aórtico (4)(5)(6)18,44) .…”
Section: Implicações Clínicasunclassified
“…Ressaltese, o uso de diuréticos, o estresse, as restrições dietéticas e a administração pré-operatória de catecolaminas contribuem significativamente para queda dos níveis circulantes de magnésio nos pacientes cirúrgicos (6,44,45) . Adicionalmente a composição do perfusato por soluções que não possuem magnésio, como a solução de Ringer, propicia queda adicional na concentração sérica de magnésio induzida pela hemodiluição (4,6,44,47) . Os fatores acima descritos são relativamente freqüentes e exacerbam a disfunção endotelial causada pela isquemia/reperfusão.…”
Section: Implicações Clínicasunclassified
See 1 more Smart Citation
“…34 For example, after cardiopulmonary bypass and in agreement with our hypothesis, the protein-bound fraction of Mg decreased consecutively to the dilutional hypoalbuminemia following surgery, without affecting the MgI levels. 35,36 Finally, in abdominal surgery, without massive transfusion and no cardiopulmonary bypass, MgI and MgT both decreased. The MgT decrease correlated with the degree of hypoalbuminemia.…”
Section: Postoperative Injured and Critically Ill Patientsmentioning
confidence: 96%